Web Media Development in Promoting the Empowerment of Songket Weaving Products in Muara Penimbung Ulu Village - Riska Wulandari; Mega Nurrizalia (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This development research aims to produce web media in the promotion of songket weaving empowerment products as a valid and practical promotional media using the ADDIE development model (analysis, design, development, implementation and evaluation) which is carried out at the Mardiah Songket Gallery in Muara Penimbung Ulu village. The data collection techniques used in this study were interviews and questionnaires. The result of this study is that web media in the promotion of songket weaving products that have a media validity level get a total value of 38 with a percentage of 95%, then the material gets a total value of 32 with a percentage of 80%, and the language gets a total score of 34 with a percentage of 94.4%. This songket weaving product empowerment promotional web has a practicality level of 95% which is very feasible. Based on the results of validation and implementation, it can be concluded that the development of web media in the promotion of songket weaving empowerment products is categorized as very valid or very feasible and practical.